Pengembangan Branding dan Digital Marketing Produk KPBS sebagai Upaya Peningkatan Daya Saing Koperasi - Nur Syafira Ramona; Rinawati; Wahyudin Bagenda; Rizki Ardiansyah Rubini (Jurnal PKM Merah Putih, 2026)
PT Susu Koperasi Peternak Bandung Selatan (KPBS) Pangalengan is a dairy cooperative engaged in the processing and marketing of fresh milk and various dairy products with considerable market potential. However, branding management and digital marketing practices have not yet been implemented in a structured and sustainable manner, resulting in limited brand visibility, ineffective communication of product identity, and restricted market reach. This Community Service Program aimed to enhance the partner’s capacity in branding development and digital marketing implementation as strategic tools for strengthening market competitiveness in the digital era. The program employed a participatory approach involving the partner as an active participant throughout the process, including needs assessment, brand identity development, digital marketing training, implementation assistance, and program evaluation. The results indicated improved understanding of the importance of branding and digital marketing in building product image and expanding market opportunities. Furthermore, the partner successfully developed a clearer brand identity direction and improved its capability to utilize digital media for promotional and marketing communication activities. The program contributed positively to strengthening the competitiveness of KPBS products and provided a foundation for the development of more sustainable marketing strategies.